Borderline testicular disease in children: What is the preferred surgical management? - Ornella Betzabe Grijalva Estrada; Verónica Vargas Cruz; Alvaro Escassi Gil; María Camila Suarez Arbeláez; Rosa María Paredes Esteban; Alberto Parente Hernandez (Elsevier, 2023)
Introduction: Management of a small testis in a child is a controversial subject. Since there are no international guidelines or at least no consensus on the treatment of this condition, there is a diverse spectrum of opinion on its management. Purpose: The two objectives of this study are (1) to identify the surgeons' preferred treatment protocol of a small testis in the pediatric patient, and (2) to determine whether the treatment of choice is influenced by the specialty of the surgeon. Materials and methods: Relevant clinical information about 5 pediatric cases was contained in a survey distributed by means of social-media and e-mails to both qualified and in-training residents practicing surgery in the urological and pediatric disciplines. An additional requirement was that the participants should have or have had regular practice in pediatric urology surgery. The chi-square-test was used in order to compare the preferred treatment protocols between the pediatric urologist practicing surgery and the pediatric surgeons. A p-value of less than 0.05 was considered significant. Results: One hundred and fifty [150] surgeons from 14 countries responded to the survey, of which 67.3% were pediatric urologists practicing surgery, 22.7% pediatric surgeons, 8.7% pediatric surgery residents, and 1.3% adult urologists.The only significant difference was observed in case #4, in which 43% of pediatric surgeons would do an orchiectomy while only 25% of pediatric urologists practicing surgery would follow this management (p = 0.007). In the other cases no significant difference was observed between surgeons practicing in the pediatric discipline and those practicing in the urological discipline. Conclusions: Treatment of borderline testicular disease varies depending on the discipline of the surgical professional whom is consulted. Nevertheless, there is not a significant difference between choices made by the pediatric urologist practicing surgery and the pediatric surgeon, apart from in the treatment of secondary testicular torsion after orchidopexy. This survey reveals that there is no single correct treatment choice of borderline testicular disease in a child. Each participant of this survey could justify their preferred treatment. It is always important to individualize the handling in each case.